2005
DOI: 10.4049/jimmunol.174.1.411
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Neutrophil IL-8 Production by Hydrogen Peroxide and Dysregulation in Chronic Granulomatous Disease

Abstract: The innate immune response to bacterial infections includes neutrophil chemotaxis and activation, but regulation of inflammation is less well understood. Formyl peptides, byproducts of bacterial metabolism as well as mitochondrial protein biosynthesis, induce neutrophil chemotaxis, the generation of reactive oxygen intermediates (ROI), and the production of the neutrophil chemoattractant, IL-8. Patients with chronic granulomatous disease (CGD) exhibit deficient generation of ROI and hydrogen peroxide and susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 30 publications
7
55
1
Order By: Relevance
“…The available reports invariably describe increased inflammatory reactions in CGD cells/patients [3,[38][39][40], and a recent microarray study described up-regulation of various proinflammatory genes in unstimulated CGD cells compared to controls [41]. Thus, the data presented in our work are consistent with these published studies and suggest that ROS exhibit a dampening effect on inflammatory reactions, which fits very well with clinical data on exuberant inflammatory responses in CGD patients [4,42,43].…”
Section: Discussionsupporting
confidence: 82%
“…The available reports invariably describe increased inflammatory reactions in CGD cells/patients [3,[38][39][40], and a recent microarray study described up-regulation of various proinflammatory genes in unstimulated CGD cells compared to controls [41]. Thus, the data presented in our work are consistent with these published studies and suggest that ROS exhibit a dampening effect on inflammatory reactions, which fits very well with clinical data on exuberant inflammatory responses in CGD patients [4,42,43].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, our findings of the inhibitory effects of ROS on caspase-1 activation agree with a proinflammatory state in CGD, because we found that the release of mature IL-1β was normal and after certain stimuli even increased in cells of CGD patients. Our data do not stand alone; they are in line with several previous studies that have demonstrated consistent up-regulation of various proinflammatory cytokines in cells isolated from CGD patients (27)(28)(29)(30). Unexpectedly, whereas we found that primary monocytes from healthy volunteers did not produce IL-1β in response to uric acid alone, monocytes from CGD patients secreted substantial amounts of IL-1β.…”
Section: Discussionsupporting
confidence: 78%
“…This view correlates with previous observations that the genetic defect of p47-PHOX enhances autoimmune encephalomyelitis and arthritis in animal models (Hultqvist et al, 2004) and leads to chronic non-infectious inflammation in chronic granulomatous disease (Morgenstern et al, 1997). Additional support for this hypothesis comes from a recently published study showing that p47-PHOX-mediated ROS negatively regulate expression of IL-8 and IL-1␤ in human neutrophils (Lekstrom-Himes et al, 2005). However, the mechanism by which ROS modulate inflammation appears to be more complex.…”
Section: Discussionsupporting
confidence: 75%